Novel Prognostic Factors Associated with Cell Cycle Control in Sporadic Medullary Thyroid Cancer Patients - Raffaele Pezzani; Loris Bertazza; Elisabetta Cavedon; Simona Censi; Jacopo Manso; Sara Watutantrige-Fernando; Gianmaria Pennelli; Francesca Galuppini; Susi Barollo; Caterina Mian (International Journal of Endocrinology)
Background. Medullary thyroid cancer (MTC) is a rare neuroendocrine-derived malignancy. It is represented by sporadic and familiar forms, and both can have RET oncogene mutations. Numerous markers can be used to define MTC; however, none is generally approved for predicting the outcome of sporadic MTC. Aim. The aim of this work was to analyze PTTG1/securin and Aurora kinase A expressions in MTC patients, both at the gene and protein levels, and to define their prognostic role in MTC assessing their association with lab and clinical parameters. Patients and Methods. Seventy-one sporadic MTC human samples were analyzed for RET mutations and by qPCR for PTTG1 and AURKA (Aurora kinase A) expression. Ki-67 levels and western blot reactivity for PTTG1 and Aurora kinase A were also determined in a selected cohort of patients. Results. RET somatic mutations were found in 48% of the patients (34/71). PTTG1 expression was statistically different among the groups with or without regional lymph node metastasis (p<0.0001) and advanced stage disease (p<0.01). PTTG1 and AURKA expressions were statistically higher than those of controls (p=0.01 and p<0.002, respectively). PTTG1 expression and Ki-67 levels were statistically different among the groups with remitted or persistent disease (p<0.05 and p<0.01, respectively). We found a significant correlation between the expressions of AURKA and PTTG1 (p<0.0002, r=0.5298) and between the expressions of PTTG1 and Ki-67 (p=0.01). Ki-67 levels were statistically different among the groups with or without metastatic lymph nodes (p=0.01) or distant metastases (p=0.003). Conclusion. The presence of an altered expression of PTTG1 and AURKA is a negative prognostic factor associated with a more aggressive course of disease, such as an advanced stage or disease persistence. It emerges as a cell cycle process mediated by the 2 factors, in addition to the RET pathway, which can be altered in MTC patients.